Effect of Sodium Chloride Salts on Benzoic Acid Solubility and Dissociation into Water at 298 K - Shiv Prakash Mishra (Progress in Chemical Science Research Vol. 1, 2022)
The effect of sodium chloride (NaCl) salt concentration on benzoic acid (C6H5COOH) solubility and dissociation in water at 298 K temperature was investigated in this research. At this temperature the benzoic acid solubility into water and their dissociation value in six range of 0.00, 0.05, 0.10, 0.30, 0.40 and 0.50 M as for each different ionic strength or concentration of sodium chloride is analyzed by titrimetrically against of 0.05 M sodium hydroxide (NaOH) solution. A calibrated pH-meter is used to accurately test the pH of each solution. The content of NaCl appears to be inversely related to the pH of benzoic acid in water at the application temperature. The value of benzoic acid’s ionic strength (I) is displayed graphically against the acid’s dissociation constant (Kc) in water at a certain 298 K temperature.